Macroalgae drying by a green process based on microwave - Gaspar, João Carlos Matias (2019)
The present work aims to demonstrate the effects of macroalgae processing, namely of the algae Ulva rigida, by microwave assisted drying. In this sense, the algae provided by the company AlgaPlus was processed in the laboratory in a microwave with a hydrodifusion and gravity configuration (NEOS-GR) whose function was to dry the algae by dehydrating them. Its function was to dry the algae by extracting the water content contained in the cells. Several different energy configurations have been defined to achieve the most cost-effective configuration. The most advantageous configuration to process 100 g of Ulva rigida was the 600 W configuration with a flash value of 0.66 at a 30 s base time which resulted in a final sample processed at a moisture content of 16 %, a colour difference of 15.72 %, when compared to the initial sample, and an energy cost of 596 J.g-1 .